2022
DOI: 10.1007/s10534-022-00455-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticular and other carriers to deliver lactoferrin for antimicrobial, antibiofilm and bone-regenerating effects: a review

Abstract: Bone and joint infections are a rare but serious problem worldwide. Lactoferrin’s antimicrobial and antibiofilm activity coupled with its bone-regenerating effects may make it suitable for improving bone and joint infection treatment. However, free lactoferrin (LF) has highly variable oral bioavailability in humans due to potential for degradation in the stomach and small intestine. It also has a short half-life in blood plasma. Therefore, encapsulating LF in nanocarriers may slow degradation in the gastrointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…Lactoferrin-based nanocarrier formulations are promising options to deliver drugs to hard-to-treat intracellular bacteria and even more challenging cases such as biofilms. , Their small size, ability to encapsulate both hydrophobic and hydrophilic drugs, and potential for targeted drug delivery are credited to this. Lactoferrin receptors are expressed on many cells including lung epithelial cells, macrophages, brain endothelial cells, liver cells, and cancer cells as well as some pathogenic bacteria, making them suitable to target therapeutic agents to these cells through receptor-mediated endocytosis. S.…”
Section: Discussionmentioning
confidence: 99%
“…Lactoferrin-based nanocarrier formulations are promising options to deliver drugs to hard-to-treat intracellular bacteria and even more challenging cases such as biofilms. , Their small size, ability to encapsulate both hydrophobic and hydrophilic drugs, and potential for targeted drug delivery are credited to this. Lactoferrin receptors are expressed on many cells including lung epithelial cells, macrophages, brain endothelial cells, liver cells, and cancer cells as well as some pathogenic bacteria, making them suitable to target therapeutic agents to these cells through receptor-mediated endocytosis. S.…”
Section: Discussionmentioning
confidence: 99%
“…Many experimental approaches have been made to evaluate how different carrier systems, such as microparticles or nanoparticles and liposomes, can improve the stability of Lf. These oral delivery systems focused on the stability of Lf recently have been extensively reviewed [ 12 , 13 , 14 ]. Using an in vitro simulated digestive model, it has been shown that bLf is sensitive to gastric digestion [ 15 ], but when it is formulated in oral carriers, the systems’ proteolysis is decreased [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Pharmacologic Of Lactoferrin Formulations: General Aspectsmentioning
confidence: 99%
“…The encapsulation of LF by using natural-based materials, e.g. polysaccharides (chitosan, alginate, pectin, gum Arabic, heparin), lipids (phospholipids, cholesterol, soy lecithin), and proteins (caseins, whey proteins, gelatin), has become one of the fast-growing trends used for improving protein bioavailability. , Although LF is considered entirely safe for humans, more detailed clinical trials are required before its inclusion in medicinal products.…”
Section: Future Perspectivesmentioning
confidence: 99%